Assessment of efficiency of breeding methods in accelerating genetic gain in rice - Biswas, Partha S.; Santelices, R.; Mendoza, Rhulyx; Lopena, Vitaliano; Arbelaez, Juan D.; Manigbas, Norvie L.; Cobb, Joshua N.; Collard, Bertrand; Islam, Mohammad Rafiqul (MDPI, 2024)
The pedigree, bulk, and single-seed descent-based rapid generation advance methods are commonly practiced breeding methods in rice. But the efficiency of these breeding methods in enhancing genetic gain has not been investigated yet. In this study, we compared the pedigree and bulk method-derived breeding lines of five crosses with RGA-derived lines. The RGA method was found to be almost two times more efficient in capturing high-yielding lines with a high breeding value and thus accelerated genetic gain much more than the bulk and pedigree methods. The RGA method is not only more efficient but also significantly cheaper (~24%) compared to pedigree methods. The cost per kilogram of genetic gain in yield for the RGA lines is almost 3 times lower than the bulk method and 4.5 times lower than the pedigree method, and it can be achieved in half the time required for line development with either the bulk or pedigree method.